2020
DOI: 10.1007/s40264-019-00899-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Overlap in Signals from EVDAS, FAERS, and VigiBase®

Abstract: Introduction The Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) and VigiBase ® are two established databases for safety monitoring of medicinal products, recently complemented with the EudraVigilance Data Analysis System (EVDAS). Objective Signals of disproportionate reporting (SDRs) can characterize the reporting profile of a drug, accounting for the distribution of all drugs and all events in the database. This study aims to quantify the redundancy among the three databases when ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…While reports by healthcare professionals and consumers are voluntary, all suspected ADRs received by marketing authorization holders regarding a product are required to be submitted to the FDA. Similar pharmacovigilance databases exist, including the European Union (EU) database EudraVigilance [ 22 ], as well as the World Health Organization (WHO) VigiBase [ 23 ], which contains all case safety reports submitted by WHO member countries [ 24 ]. While the geographical region of focus is different between these databases, with FAERS predominantly covering the US, EudraVigilance covering the European Union, and VigiBase with a global focus, previous studies have identified overlapping results [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…While reports by healthcare professionals and consumers are voluntary, all suspected ADRs received by marketing authorization holders regarding a product are required to be submitted to the FDA. Similar pharmacovigilance databases exist, including the European Union (EU) database EudraVigilance [ 22 ], as well as the World Health Organization (WHO) VigiBase [ 23 ], which contains all case safety reports submitted by WHO member countries [ 24 ]. While the geographical region of focus is different between these databases, with FAERS predominantly covering the US, EudraVigilance covering the European Union, and VigiBase with a global focus, previous studies have identified overlapping results [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The findings of our study may not be generalizable to other databases due to differences related to the database background and the medical products covered. Nevertheless, several studies have highlighted the similitudes and overlaps between SDR found from pharmaceutical company databases and international pharmacovigilance databases (Candore et al, 2015;Vogel et al, 2020). Finally, while it can be assumed that the results are applicable to other drug events pairs, the predicted probabilities calculated in this study are not extrapolable.…”
Section: Discussionmentioning
confidence: 85%
“…21 Nevertheless, recent studies show similar sensitivity for EudraVigilance compared to other databases for safety monitoring of medicinal products such as VigiBase or the FDA Adverse Event Reporting System. 22 Fourth, the mean latency period was 15.3 months. Nevertheless, data were not available for almost half of the reports.…”
Section: Discussionmentioning
confidence: 94%
“…We could not gather information about the body mass index, which is a known risk factor for developing bladder cancer 21 . Nevertheless, recent studies show similar sensitivity for EudraVigilance compared to other databases for safety monitoring of medicinal products such as VigiBase or the FDA Adverse Event Reporting System 22 . Fourth, the mean latency period was 15.3 months.…”
Section: Discussionmentioning
confidence: 95%